Early recruitable coronary collaterals preserve miocardial viability in late presentation infarctions. Issue 6 (11th July 2022) - Gutiérrez-Barrios, Alejandro; Alarcón de la Lastra, Inara; Cañadas-Pruaño, Lola; Delgado, William; Alba-Sáchez, Miguel; Gamaza-Chulián, Sergio; Díaz-Retamino, Enrique; Zayas-Rueda, Ricardo; Calle-Pérez, Germán; Vázquez-García, Rafael; Toro, Rocio
Abstract : Background: Previous studies showed conflicting results regarding the contribution of coronary collateral circulation (CCC) to myocardial perfusion and function in the setting of myocardial infarction (MI). In the primary angioplasty era, the role of CCC in these studies may have been influenced by the effect of early reperfusion. The true impact of CCC could be clarified by studying its effect on nonreperfused patients. The aim of our study was to evaluate the effect of CCC on myocardial viability of late presentation MI. Methods and results: Between 2008 and 2019, we included 167 patients with a late presentation MI who had a complete angiographic occlusion in a major coronary artery in which myocardial viability of the culprit territory was assessed. Patients were divided according to the presence of angiographic early recruited CCC (ERCC) (Rentrop 2–3) or poor CCC (PCC) (Rentrop 0–1). A lower left ventricular ejection function (LVEF) at discharge (54.2 ± 9 vs. 47.9 ± 12; <0.01) and a more severe left ventricular wall motion abnormalities in the culprit territory were observed in PCC patients. The presence of ERCC was the main independent predictor of myocardial viability in late presentation MI (hazard ratio, 4.24; 95% confidence interval, 1.68–10.6; P < 0.001). At follow-up, wall motion score increased significantly (2.05 ± 0.16; P = 0.02) in patients with ERCC but not in PCC patients (0.07 ± 0.16; P = 0.4), and LVEF improvement was significantly higher in ERCC than in PCC patients (9.7 ± 2.6 vs. 3.8 ± 4.2; P = 0.02). Conclusion: The presence of ERCC was the main independent predictor of myocardial viability in late presentation MI.